Zmiany jeziorności w środkowym i dolnym dorzeczu Warty od XIX wieku - Ptak, Mariusz (My University, 2010)
Praca nawiązuje do głównych problemów limnologii: zmian jeziorności, zmian powierzchni jezior oraz przyczyn tych zmian. Przeprowadzona analiza dotyczy dolnego i środkowego dorzecza Warty, stanowiącego około 10% kraju. Opracowano ją w oparciu o materiał kartograficzny (mapy topograficzne z końca XIX wieku oraz mapy topograficzne z końca XX wieku), w przedziale czasowym wynoszącym 110 lat. Uzyskane wyniki pokazują znaczny spadek zarówno wskaźnika jeziorności (o 10.7%), powierzchni jezior (o 10,8%) oraz liczby jezior (o 15,5%). Na podstawie analizy statystycznej ustalono, że największy związek występuje pomiędzy zanikiem powierzchni jezior a jeziorami najmniejszymi (1-5 ha).

The present work touches upon the main problems of limnology: the disappearance of lakes, the pace at which this process occurs as well as its causes. It has analyzed the changes in lake density in the lower and middle Warta river basin. The hydrographic analysis of this area is particularly interesting – it focuses on inland stagnant waters owing to the postglacial character of the terrain (characterized by a large number of lakes) – the highest recorded water deficits in the country, and the economic advancement. The total lake area was calculated for the years 1890 and 2000, based on 1:25000 and 1:50000 scale topographic maps. They served as the basis for calculating changes which occurred in the course of 110 years. The following information was gathered on the basis of the maps from the earlier period: 2066 (100%) lakes with the area of 1 ha or more. The total lake area amounted to 62054.9 ha (100%). Lake density in the lower and middle Warta river basin at the end of the 19th century amounted to 1.78 (100%). The analysis of the data from the topographic maps edited at the end of the 20th century revealed the presence of 1744 (84.4%) lakes. The total lake area was 55365.5 ha (89.2%), while lake density totaled 1.59 (89.3%).
Changes in lake percentage in the middle and lower Warta River Basin since 19 th century
Wydział Nauk Geograficznych i Geologicznych: Instytut Geografii Fizycznej i Kształtowania Środowiska Przyrodniczego
Keywords: zmiany jeziorności; lake percentage; zmiany powierzchni jezior; disappearance of lake; dorzecze Warty; Warta River Basin